2014
DOI: 10.1016/j.neurobiolaging.2013.11.028
|View full text |Cite
|
Sign up to set email alerts
|

A right hemisphere role in cognitive reserve

Abstract: High levels of education, occupational complexity and/or premorbid intelligence are associated with lower levels of cognitive impairment than would be expected from a given brain pathology. This has been observed across a range of conditions including Alzheimer's Disease (Roe, et al., 2010), stroke (Ojala-Oksala, et al., 2012), traumatic brain injury (Kesler, et al., 2003), and penetrating brain injury (Grafman, 1986). This cluster of factors, which seemingly protect the brain from expressing symptoms of damag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

25
164
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(190 citation statements)
references
References 140 publications
25
164
1
Order By: Relevance
“…Beyond modulating and potentially improving treatment outcomes, sustained attention abilities have been associated with multiple aspects of daily living and functional outcomes including academic achievement (Steinmayr, Ziegler, & Träuble, 2010), driver safety and accidents (Edkins & Pollock, 1997; Yanko & Spalek, 2014), and the ability to develop effective social communication skills (Bennett Murphy, Laurie‐Rose, Brinkman, & McNamara, 2007). Additionally, recent developments have suggested that sustained attention ability may provide a gating mechanism that helps to preserve general cognitive abilities during neurodegeneration associated with aging (Robertson, 2013, 2014; Wilson et al., 2013). Collectively, these findings suggest that above and beyond any emotional disturbances that may be associated with early life trauma, concurrent deficits in sustained attention ability can negatively impact multiple facets of an individual's life throughout the lifespan.…”
Section: Discussionmentioning
confidence: 99%
“…Beyond modulating and potentially improving treatment outcomes, sustained attention abilities have been associated with multiple aspects of daily living and functional outcomes including academic achievement (Steinmayr, Ziegler, & Träuble, 2010), driver safety and accidents (Edkins & Pollock, 1997; Yanko & Spalek, 2014), and the ability to develop effective social communication skills (Bennett Murphy, Laurie‐Rose, Brinkman, & McNamara, 2007). Additionally, recent developments have suggested that sustained attention ability may provide a gating mechanism that helps to preserve general cognitive abilities during neurodegeneration associated with aging (Robertson, 2013, 2014; Wilson et al., 2013). Collectively, these findings suggest that above and beyond any emotional disturbances that may be associated with early life trauma, concurrent deficits in sustained attention ability can negatively impact multiple facets of an individual's life throughout the lifespan.…”
Section: Discussionmentioning
confidence: 99%
“…A combination of higher education, higher estimated verbal IQ, and higher occupational complexity have been found to comprise what has been termed “cognitive reserve”, which is thought to be the ability to optimize normal cognitive performance 44 , and may serve as a protective factor from the expression of neuropathology 45,46 .…”
Section: Methodsmentioning
confidence: 99%
“…This is coherent with the vast neuroimaging literature pointing to the existence of early, sensory bottlenecks in information processing -mainly related to short-term memory limits within each modality (Linden, 2007;Marois & Ivanoff, 2005) -and a more general, amodal fronto-parietal network acting as a central information relay and sensibly limiting our efficiency in multitasking (Dux, Ivanoff, Asplund, & Marois, 2006;Spence, 2008;Tombu et al, 2011). Nevertheless, these domain-general, non-lateralized factors (which are also relevant for the notion of cognitive resources/reserve; Stern, 2002) are thought to be associated with right-hemisphere mechanisms (Corbetta & Shulman, 2011;Robertson, 2014).…”
mentioning
confidence: 99%